Evolution of physiological dormancy multiple times in Melastomataceae from Neotropical montane vegetation - Silveira, Fernando A.O.; Ribeiro, Rafaella C.; Oliveira, Denise M.T.; Fernandes, G. Wilson; Lemos-Filho, José P. (Seed science research, 2012)
We investigated seed dormancy among species of Melastomataceae from Neotropical montane vegetation of Brazil. Four out of 50 studied species had dormant seeds: Miconia corallina (Miconieae), Tibouchina cardinalis (Melastomeae), Comolia sertularia (Melastomeae) and Chaetostoma armatum (Microlicieae). For these four species, germinability of seeds collected in different years was always < 10% and the percentages of embryoless seeds and non-viable embryos were both insufficient to explain low or null germinability. This is the first unequivocal report of seed dormancy in tropical Melastomataceae. The production of seeds with permeable seed coats and fully developed, differentiated embryos indicates the occurrence of physiological dormancy. The reconstructed phylogenetic tree of the 50 species suggests that physiological dormancy evolved multiple times during the evolutionary history of Melastomataceae in this vegetation. Physiological dormancy evolved in species and populations associated with xeric microhabitats, where seeds are dispersed in unfavourable conditions for establishment. Therefore, drought-induced mortality may have been a strong selective pressure favouring the evolution of physiological dormancy in Melastomataceae. We argue that dormancy may have been independently selected in other lineages of Cerrado plants colonizing xeric microhabitats and dispersing seeds at the end of the rainy season. The contributions of our data to the understanding of seed dormancy in tropical montane vegetation are discussed.